Fiscal policy coordination in the EMU: A problem with asymmetry and aggregation - Matti Viren (Aboa Centre for Economics (ACE), 2011)
This paper deals with fiscal policy coordination within the European Monetary Union. In the first place, it investigates the potential problems which are caused by cross-country differences in key fiscal parameters and the asymmetric nature of these parameters. In the second section, the pros and cons of policy coordination evaluated using some multi-country estimates as point of reference. The empirical results clearly show that policy coordination within the EMU context is very difficult because of these country differences and asymmetries. Even so, it is shown that policy coordination pays off at least in cases where the countries share the same shocks. Some practical problems of policy coordination and future prospects are also considered in the paper.
Keywords: H62; E61; E63; 330; Fiscal policy; policy coordination; government deficit; EMU